Revisão da hipótese de monofiletismo da família Aplocheilidae, Bleeker (Cyprinodontiformes - Aplocheiloidei) - D'Arrigo, Rosana Cristina Pezzi (2001)
The hypothesis of monophyly and inter relationships of the family Aplocheilidae are reexamined. The analysis is based on morphology, primarily osteology, of 25 species. It includes 130 characters, of which 34 are new; 30 are personal communications by Costa and the remaining are from Parenti's (1981) and Costa's (1998 a and b) phylogenetic studies. The strict consensus tree obtained from the 13 equally most parsimonious cladograms (consistency índex 0.60, retention índex 0.79, length, 294) has the following topology: (Rivulus caudomarginatus ((Epiplatys sangmelinensis ((Epiplatys bifasciatus; Epiplatys fasciolatus)(Epiplatys chaperi; Epiplatys mesogramma))(Nothobranchius guentheri ((Aphyosemion aureum) (Aphyosemion bivittatum) (Aphyosemion herzogi) (Aphyosemion cameroensis) (Aphyosemion petersi; Aphyosemion guignardi)(Fundulopanchax splendidum; Fundulopanchax gulare)) (Pachypanchax playfairi (Aplocheilus panchax (Aplocheilus blocki (Aplocheilus lineatus(Aplocheilus dayi Aplocheilus werneri))))). Monophyly of Aplocheilidae is supported. The present phylogenetic hypothesis differs from that of Parenti's (1981) in the proposed sister group relationship between Epiplatys and the clade comprising the genera Aphyosemion, Fundulopanchax and Nothobranchius instead of Epiplatys being n the sister group relationship to the genera Aplocheilus and Pachypanchax. In this aspect it agrees with the Murphy and Collier's (1997) hypothesis. Comparison between the present hypothesis, that one from Parenti's (1981) analysis and the other one from Murphy and Collier's (1997) analysis are made.